INTERMEDIATE UVEITIS AS THE FIRST PRESENTATION OF MULTIPLE SCLEROSIS - Trpeska, Ana; Antovic, Svetozar; Joksimovic, Marija; Joksimovic, Vladimir; Skeparovska, Kristina (Journal of Morphological Sciences; Vol 3 No 2 (2020): JMS, 2020)
Intermediate uveitis is a chronic, relapsing disease of insidious onset in which according to the SUN Working Group, the vitreous is the primary site of inflammation as determined clinically. Intermediate uveitis associated with systemic disease has variable course. Multiple sclerosis is associated with intermediate uveitis. We report a case of multiple sclerosis were intermediate uveitis was the first presentation of the disease. A 33-year-old man with a 5 months history of decreased vision in his right eye. Best-corrected visual acuity was 0.6 on his right eye and 1.0 on his left eye. Intraocular pressure was 17 mmHg and 15 mmHg on the right and left respectively. He had no signs of ocular surface inflammation, cornea clear, AC without signs of inflammation, lens clear. Right eye 3+ vitreous cells and vitreous condensations left eye 1+vitreous cells. Right eye fundus showed  hyperemia of optic nerve head, irregular reflexes in the macula, peripheral retina without signs of retinitis or vasculitis. Left eye  fundus showed only optic nerve head slightly hyperaemic. OCT, Indocyanine Green Angiography and fluorescein angiography were performed.   We performed the investigations for diagnosing uveitis (angiotensin converting enzyme, serology for Treponema pallidum, Borrelia burgdorferi, Mantoux, neurological investigation) and all turned out to be negative except of MRI Brain and Spine that revealed multiple T2 hyperintense lesions consistent with multiple sclerosis. Multiple sclerosis may present initially with an intermediate uveitis. Multiple sclerosis should be suspected in patients aged 20-50 even without any neurological symptoms, noting that intermediate uveitis  may precede other symptoms of demyelination. Key words : intermediate uveitis, multiple sclerosis, vitritis